دور القيادة الادارية في تحقيق الابداع الاداري : دراسة حالة شركة سكر كنانة المحدودة ٢٠٢٣ م - د. کمال احمد محمد عبد الله (White Nile Journal for Studies and Research, 2024)
The problem of the study was to answer the following question: What is the role of administrative leadership in achieving administrative creativity in the Kenana Sugar Company Limited? The study aimed to identify the concepts of administrative leadership styles and administrative creativity, to identify the most interactive leadership styles in the process of administrative creativity, and to reveal the most important leadership styles that help in the process of administrative creativity. The study used the descriptive analytical approach. The study assumed the following hypotheses: There is a statistically significant relationship between the style of bureaucratic leadership and the achievement of administrative creativity. There is a statistically significant relationship between the style of democratic leadership and the achievement of administrative creativity. There is a statistically significant relationship between the style of free leadership and the achievement of administrative creativity. The most important findings of the study: There is a statistically significant relationship between the style of administrative leadership and administrative creativity at Kenana Sugar Company Limited. The most important recommendations are: Organizations should work on training their leaders to increase their skills in line with modern leadership styles, that the institution should work on adopting a strategic view to apply the philosophy of leadership styles that contribute to supporting the institution towards environmental changes surrounding it, the researcher recommends the need to adopt studied and effective methods to activate and qualify the leader management to help him adapt to sudden changes. Keywords: administrative leadership administrative creativity, leader, Organization